Hanbury and Martin modern equity - Glister, James; Lee, James, 1983-; Hanbury, Harold Greville, 1898-1993. (2015)
This text gives an overview of significant cases to provide students with the facts they need and a clear explanation of difficult points.
Trusts and powers -- Trustees and fiduciaries -- Personal and proprietary claims -- Miscellaneous equitable remedies and doctrines
Originally published: London : Stevens and Sons, 1935
Includes index.
Keywords: Equity -- England; Law; Equity; England